An integral multinomial approach to understand farm succession in Costa Rica - Rodríguez Lizano, Víctor (2020)
The vast majority of quantitative studies aimed at explaining family farm succession are based on binary response models. Usually these models have exhibited low explanatory power, which has been attributed to the fact that they generally take into account only socioeconomic variables and simplify a phenomenon as complex as agricultural family succession to only two possible answers. Given the abovementioned situation, the main objective of this research was to analyze the weight of three types of variables on family farm succession. These three variables are: Socioeconomic variables, the level of the Generational Integration Process and psychological variables. The fieldwork was conducted in Zarcero, Costa Rica, with a total of 126 horticultural farmers. The probability of succession was divided into three levels: very high, medium and very low. The data were analyzed through three multinomial models. The model that included the three types of variables mentioned above is the one that best predicts the succession (79% correct prediction). Likewise, model III, which only includes psychological variables and the level of the Generational Integration Process, better explains the succession than that (model II) that only takes into account socioeconomic variables. These results represent a step forward in the way family farm succession is studied, since it was determined that the psychological factors and those related to the inclusion of young people on the farm are those that best explain agricultural family succession.